THE ROLE OF AROMATHERAPY IN PAIN MANAGEMENT DURING THE FIRST STAGE OF LABOR: A LITERATURE REVIEW - Johan, Herni; Mayangsari, Nindya (Proceeding of International Conference on Multidisciplinary Research, 2024)
Background: Pain thresholds vary among mothers during childbirth, leading to differences in their pain experiences. The intensity of labor pain can increase if the mother experiences excessive anxiety and fear. One effective non-pharmacological approach to reducing pain intensity is the use of aromatherapy. Objective: This study aims to gather information on the effectiveness of pain management during the first stage of labor using aromatherapy. Methods: The study follows a systematic review of literature, evaluating non-pharmacological pain management methods during labor. Results: Complementary therapies, such as aromatherapy, have been shown to help reduce labor pain intensity. Commonly used aromatherapy oils in this context include lavender, rose, and bitter orange. Conclusion: Understanding techniques to reduce labor pain is crucial for expectant mothers, as it helps to alleviate anxiety and fear associated with the childbirth process